2021
DOI: 10.1186/s12889-021-11610-1
|View full text |Cite
|
Sign up to set email alerts
|

Examining the relationship between food insecurity and causes of injury in Canadian adults and adolescents

Abstract: Background Food insecurity, as an indicator of socioeconomic disadvantages and a determinant of health, may be associated with injury by increasing risk exposure and hampering risk mitigation. We examined the association between food insecurity and common causes of injury in the general population. Methods Linking the Canadian Community Health Survey 2005–2017 to National Ambulatory Care Reporting System 2003–2017, this retrospective cohort study e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
(78 reference statements)
0
6
0
1
Order By: Relevance
“…As such, food insecurity deserves special attention among the set of basic needs that are required to survive. Although we did not test it in our study, the idea that food insecurity leads to opioid use has been supported by many recent studies (Men et al 2021; Men, Urquia, and Tarasuk 2021). However, it is likely that opioid-related deaths have a negative effect on other forms of material hardship.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…As such, food insecurity deserves special attention among the set of basic needs that are required to survive. Although we did not test it in our study, the idea that food insecurity leads to opioid use has been supported by many recent studies (Men et al 2021; Men, Urquia, and Tarasuk 2021). However, it is likely that opioid-related deaths have a negative effect on other forms of material hardship.…”
Section: Discussionmentioning
confidence: 73%
“…However, more recent work has found that food insecurity is associated with an increased risk of injuries, chronic pain, and use of prescription opioids, suggesting that the causal pathway may also flow in the opposite direction (Men et al 2021; Men, Urquia, and Tarasuk 2021). Thus, it is likely that the causal direction flows in both directions between food insecurity and opioid use.…”
Section: The Connection Between Food Insecurity and The Opioid Crisismentioning
confidence: 99%
See 1 more Smart Citation
“…Household food insecurity, inadequate or insecure access to food due to financial constraints, is a serious population health problem in Canada, linked to poorer men tal health, 14 higher rates of infectious 5 and noncommunicable diseases 6,7 and inju ries, 8 increased health care utilization, 912 and premature mortality. 13 Monitored since 2005 with the wellvalidated Household Food Security Survey Module (HFSSM) on the Canadian Community Health Survey (CCHS), 14 this problem was widespread and growing before the pandemic.…”
Section: Tweet This Articlementioning
confidence: 99%
“…Based on the 2018 Canadian Community Health Survey, the most recent nationally representative data available, one in five 12-17 year-olds lived in a household affected by some level of food insecurity, compared to one in ten adults 50-64 years of age and almost one in twenty adults 65 and older (Polsky & Garriguet, 2022). Although the health implications of food insecurity for adolescents have not been studied as extensively as those for adults in this country, adolescents in food-insecure households in Canada have poorer quality dietary intakes (Hutchinson & Tarasuk, 2021), higher odds of mental health problems (Men et al, 2021a;Ovenell et al, 2022), and higher incidence of injuries (Men et al, 2021b) compared to adolescents in food-secure households. In the United States, where there has been considerably more research on the relationship between household food insecurity and the health of children and youth, food insecurity among adolescents has been shown to increase their odds of elevated blood pressure and prediabetes (Lee et al, 2019), dyslipidemia (Tester et al, 2016), iron-deficiency anemia (Eicher-Miller et al, 2009), and lower bone mass (Eicher-Miller et al, 2011).…”
Section: Introductionmentioning
confidence: 99%